2004
DOI: 10.1542/peds.114.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Specific Newborn Individualized Developmental Care and Assessment Program Movements Are Associated With Acute Pain in Preterm Infants in the Neonatal Intensive Care Unit

Abstract: Objective. The Newborn Individualized Developmental Care and Assessment Program (NIDCAP) is widely used in neonatal intensive care units and comprises 85 discrete infant behaviors, some of which may communicate infant distress. The objective of this study was to identify developmentally relevant movements indicative of pain in preterm infants.Methods. Forty-four preterm infants were assessed at 32 weeks' gestational age (GA) during 3 phases (baseline, lance/squeeze, and recovery) of routine blood collection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 52 publications
4
86
1
5
Order By: Relevance
“…This reflect the efficacy of researcher teaching to nursing staff at NICU about the importance of adopting developmentally positioning during their nursing intervention using available materials as rolled linen which also eliminate control group pain score. This finding was in agreement with the result of Holsti, Grunau, Oberlander, and Whitfiels (2014) [26] who found in their study that, the distress and pain scores associated with diaper change was significantly less during the nested condition compared with the non-nested.…”
Section: Discussionsupporting
confidence: 93%
“…This reflect the efficacy of researcher teaching to nursing staff at NICU about the importance of adopting developmentally positioning during their nursing intervention using available materials as rolled linen which also eliminate control group pain score. This finding was in agreement with the result of Holsti, Grunau, Oberlander, and Whitfiels (2014) [26] who found in their study that, the distress and pain scores associated with diaper change was significantly less during the nested condition compared with the non-nested.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, infants who were sicker earlier during the neonatal period (SNAP-II on day 1) displayed more facial reactions (Holsti et al, 2004). found that greater illness severity (SNAP-II) was significantly associated with lower heart rate variability in the very low gestational age group of infants born between 29 and 32 weeks of gestational age.…”
Section: Clinical Painmentioning
confidence: 91%
“…According to the results of Holsti et al (2004), infants born at a gestational age of <30 weeks (gestational age 25-30 weeks of gestational age) showed more behavioral responses (i.e., facial and body activity from the NIDCAP) during a heel lance procedure compared with older infants (gestational age 30-32 weeks of gestational age). Evans et al (2005) found that, according to a multidimensional pain measure reflected by Premature Infant Pain Profile (PIPP) scores, infants born at 27-30 weeks and infants born at 33-36 weeks of gestational age showed significantly less physiological and behavioral responses during hospitalization in the NICU than infants born at 31-33 weeks of gestational age.…”
Section: Clinical Painmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Moreover, these behavioral signs have recently been validated with a conventional pain assessment. 36 On the basis of such observations, current developmental goals for each infant are formulated. Caregiving plans, including recommendations concerning individualized care and environmental changes based on the current developmental stage of the infant and the needs of the family, are designed.…”
Section: Family-centered Carementioning
confidence: 99%